Fish Nutritional Value as an Approach to Children's Nutrition - Maulu, Sahya; Nawanzi, Kundananji; Abdel-Tawwab, Mohsen; Khalil, Hala Saber (Frontiers in Nutrition, 2021)
Fish is one of the cheapest and most accessible sources of animal protein for human consumption even in rural communities. Therefore, promoting and increasing the consumption of fish in children could be one of the most powerful tools in the fight against malnutrition in children. Polyunsaturated fatty acids (PUFAs) are essential fatty acids present in the brain and retina that have important physiological functions. PUFAs must thus be supplied to children, as they are crucial for the maintenance and development of fetuses, neonates, and infant brains. Omega-3 reduce the risk of coronary artery disease and improve blood flow. Anti-inflammatory effects have been found in PUFAs, and they have been proven to decrease chronic inflammation in diseases including autoimmune and neurodegenerative illnesses. DHA also serves as an extra-and intracellular transcription factor, and blood DHA levels have been related to improved neurological development and visual in children. EPA can stimulate the regeneration process of remyelination and cure multiple sclerosis of the CNS, after toxic damage to CNS oligodendrocytes. PUFAs' supplementation can help children with attention problems enhance their brain development and reading abilities.